The Analysis of SGOT, SGPT, and ALP in Chili Farmers Exposed to Pesticides in Kendalbulur Village, Tulungagung - Chalies Diah Pratiwi; Andyanita Hanif Hermawati; Nosa Ika Cahyariza (Prisma Sains: Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram)
Chili farmers in Kendalbulur Village are the main subjects that have a great influence due to exposure to pesticide residues (toxicity). Pesticide toxicity affects enzymes produced by the liver that cause changes in its working system. This study aims to look at the characteristics and levels of the enzymes SGOT, SGPT, and ALP in chili farmers exposed to pesticides that perform spraying activities. The SGOT-SGPT liver function test is a health screening that combines the examination of SGOT and SGPT enzyme levels in the blood. The purpose of this liver function test is to detect hepatitis or cirrhosis of the liver in chili farmers. The alkaline phosphatase (ALP) enzyme test is conducted to help diagnose and evaluate cirrhosis and inflammatory diseases of the liver. In addition to evaluating liver function, the alkaline phosphatase (ALP) enzyme test can also help detect bone disorders or protein deficiencies in chili farmers. Respondents were 20 chili farmers and pesticide users with an age range of 34–71 years. Test method using the non-analytical descriptive method and sampling technique using total sampling. The examination carried out is the rate of SGOT, SGPT, and ALP using spectrophotometry. The results of the SGOT examination showed that all respondents had SGOT levels in the normal range of <40 U/L, where the lowest result was 16 U/L and the highest was 35 U/L. While SGPT showed that all respondents were in the normal range of 40 U/L, with the lowest result of 2 U/L and the highest of 23 U/L, the ALP levels of many respondents were above normal values. The lowest value is 131 U/L, and the highest is 222 U/L. The results showed that the respondents showed disruption of the liver because ALP levels give high results. Where should ALP levels decrease with age.